A systematic review on the effectiveness of unstandardized mindfulness interventions in improving dietary and physical activity outcomes in healthy adults - Christian E. Preissner; Lieke Vilier; Nora C. Bertelsmann; Kim Beckers; Dennis de Ruijter; Hein de Vries; Anke Oenema (BMC Public Health)
Abstract Background Mindfulness-based strategies are increasingly applied outside of standardized clinical protocols to promote healthy lifestyle behaviors. No overview exists of how mindfulness-based strategies are integrated in these “unstandardized” interventions and which strategies have potential for effect. This review (i) summarizes key intervention characteristics and strategies, (ii) provides a qualitative overview of the effectiveness of unstandardized mindfulness-based strategies for promoting healthy dietary and PA behaviors, and (iii) provides an assessment of the study quality. Methods Articles were identified using the PubMed, PsycINFO, and Web of Science online databases until 11/2024. Records were included if they applied mindfulness outside of a standardized clinical protocol among healthy adults and measured healthy dietary or PA outcomes pre- and post-intervention. Study quality was assessed using the Effective Public Health Practice Project tool. Results Interventions (n = 44) inconsistently applied formal and informal mindfulness strategies and a variety of meditation exercises (e.g., body-centered or movement meditation). The findings did not provide clear evidence in favor of unstandardized mindfulness applications in promoting dietary behaviors and PA at the between-group level. Study quality was predominantly rated as ‘weak’ due to selection bias and lacking blinding procedures. Discussion There exist great variations in the implementation of mindfulness strategies, low study quality, and heterogeneity in measurement, potentially explaining the lack of effects of such unstandardized interventions. To gain more insight into the effective application of mindfulness-based strategies in health promotion, higher-quality studies with robust designs as well as component studies are needed to shed light on the active ingredients of interventions.